Bacterial Sirtuins Overview: An Open Niche to Explore - Gallego-Jara, Julia; Ortega, Álvaro; Lozano Terol, Gema; Sola Martínez, Rosa A.; Cánovas Díaz, Manuel; de Diego Puente, Teresa (Frontiers in Microbiology, 2021)
Sirtuins are deacetylase enzymes widely distributed in all domains of life. Although for decades they have been related only to histones deacetylation in eukaryotic organisms, today they are considered global regulators in both prokaryotes and eukaryotes. Despite the important role of sirtuins in humans, the knowledge about bacterial sirtuins is still limited. Several proteomics studies have shown that bacterial sirtuins deacetylate a large number of lysines in vivo, although the effect that this deacetylation causes in most of them remains unknown. To date, only the regulation of a few bacterial sirtuin substrates has been characterized, being their metabolic roles widely distributed: carbon and nitrogen metabolism, DNA transcription, protein translation, or virulence. One of the most current topics on acetylation and deacetylation focuses on studying stoichiometry using quantitative LC-MS/MS. The results suggest that prokaryotic sirtuins deacetylate at low stoichiometry sites, although more studies are needed to know if it is a common characteristic of bacterial sirtuins and its biological significance. Unlike eukaryotic organisms, bacteria usually have one or few sirtuins, which have been reported to have closer common ancestors with the human Sirt5 than with any other class. In this work, in addition to carrying out an in-depth review of the role of bacterial sirtuins in their physiology, a phylogenetic study has been performed that reveals the evolutionary differences between sirtuins of different bacterial species and even between homologous sirtuins.